Há associação entre a estrutura, organização e acesso aos serviços de saúde bucal ofertados na atenção básica no estado da Paraíba segundo porte populacional dos municípios? - Limão, Nayara Pereira (2023)
The evaluation of services is structured as a tool that assists management and organization of services, contributing to health decision-making. The Ministry of Health established the National Program for Improving Access and Quality of Primary Care (PMAQ-AB), with the aim of improving the quality and access to health services. The program started in 2011 and ended in 2019, where three cycles were carried out. The present study, of an observational, analytical and cross-sectional nature, with a secondary basis, aims to analyze whether the structure of UBS and the organization of eSB are associated with access to dental care offered in PC in Paraíba, considering the population size of the municipalities, according to the data from the 3rd PMAQ-AB external evaluation cycle. Module III - (Interview with the user at the UBS) was used to analyze access to services; Module V- (Observation at the UBS), to check the infrastructure of the units and Module VI (Interview with the eSB professional and verification of documents at the UBS), to analyze the organization of the teams' work process. Descriptive analysis and inferential analysis were carried out using logistic regression, considering the outcome variable relating to access as “Are you able to schedule an appointment with the dentist at this health unit?”. Odds Ratios (OR) were estimated for the outcome, considering α=0.05. The model was adjusted using the Hosmer and Lemeshow test. As a result, it was observed that almost all users of PC in Paraíba are able to schedule an appointment with the dentist, with a higher percentage found for users in small municipalities (98.1%). The regression models demonstrated the following associations for the model referring to small municipalities I: the UBS does not have anesthetics without vasoconstrictors (OR=2.86) and the team's clinical care does not guarantee scheduled/scheduled care (OR=4 ,26). For the model referring to small municipalities II: the presence of exposed, loose or bare wires (OR= 0.11). For medium-sized municipalities: the UBS does not have calcium hydroxide cement (OR=7.28) and cleaning material for instruments and drills in sufficient quantities (OR= 31.29). For the model referring to large municipalities, the associated factors were: the UBS not having topical anesthetics (OR=8.18); metallic matrix (OR=18.76); light-cured resins (OR=4.37); there is no reservation of places in the eSB agenda, a time that is easily accessible to the professional so that the user can search for and show exam results (OR=9.47) and the eSB professionals do not carry out reception jointly with the PC team (OR =3.65).It is concluded that the factors associated with the structure, organization and access to oral health services differ according to the group of municipalities and their respective population characteristics. There is a need for differentiated attention, with reorganization of the work process, considering the particularities of each group of municipalities in Paraíba.